Linguodidactic principles of teaching foreign languages using digital applications - Bahridinova , Mutabarhan (The Lingua Spectrum, 2025)
In recent years, digital technologies have been rapidly integrated into educational systems, significantly transforming teaching methodologies. This is particularly evident in the field of teaching German as a foreign language (DaF), where electronic learning tools are increasingly becoming an essential component of the instructional process. This article examines current trends in digital education, explores challenges related to improving instructional quality, and underscores the need for innovative approaches to content development and teaching formats. From a linguodidactic standpoint, the paper emphasizes the importance of a well-reasoned and systematic application of digital technologies to enhance the overall effectiveness of language instruction.